ANALISIS KEBUTUHAN AIR IRIGASI PADA PERTUMBUHAN TANAMAN KAPAS (Gossypium hirtusum L.) DI KECAMATAN LAMURU, KABUPATEN BONE - Junaedi Junaedi; Syahruni Thamrin; Baso Darwisah; Budiman Budiman (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2020)
The development of cotton crop in South Sulawesi is still constrained by the availability of water which is affected by rainfall and the ability of the soil to retain water, so to optimize the growth of cotton crop needs to be done special methods of giving water. This study aims to analyze the irrigation water needs and maximize the yield of cotton crop production by using Cropwat 8.0 application as an alternative calculation of water demand. Analysis of the calculation of irrigation water needs of cotton crop with Cropwat 8.0 is intended as a basis for determining the amount of water that will be applied to irrigation activities and providing irrigation water. The results of the analysis of the water needs of cotton crop are calculated based on the growth phase of cotton crop showed a reference evapotranspiration value (ETo) calculated with a cropwat 8.0 program ranging from 3.12 - 4.53 mm/day and plant evapotranspiration (ETc) values ranging from 1.06 - 4.56 mm/day. Effective rainfall ranges from 5.9 - 15.7 mm/month. The total amount of water was applied for cotton crop is 512.5 mm. The irrigation water requirement was 213.3 mm. The maximum amount needed per month is 19 mm.